Return Plans and Migrants' Behavior - Bastien Chabé-Ferret; Joel Machado; Jackline Wahba (Institute for the Study of Labor (IZA), 2016)
This paper studies how return migration intentions affect immigrants' behavior. Using a unique French data set, we analyze the relationship between return plans and several immigrants' behavior in the host and origin countries addressing the potential endogeneity between return plans and different investment decisions. We also investigate the potential trade-off and complementarities between various immigrants' investment behaviors. We find that temporary migrants are more likely to remit and invest in the country of origin, but less likely to invest in the host country. Moreover, our results show that there is no trade-off between immigrants' investment in the home and in the host country. In turn, we find substantial heterogeneity in behavior across migrants of different origins.
Keywords: F22; F24; D14; 330; temporary migration; return intention; remittances